2007
DOI: 10.1093/humrep/dem254
|View full text |Cite
|
Sign up to set email alerts
|

Serum anti-mullerian hormone and estradiol levels as predictors of ovarian hyperstimulation syndrome in assisted reproduction technology cycles

Abstract: The basal serum AMH level could be utilized effectively to predict OHSS and thus to direct the selection of mild COS protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
111
4
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(137 citation statements)
references
References 37 publications
10
111
4
8
Order By: Relevance
“…Firstly, recent studies have suggested that women with high levels of AMH are at considerably increased risk of developing OHSS [15,18,38,39]. A clinician may use this information to reduce the starting dose of FSH in such "high risk" patients, thereby reducing their chances of developing OHSS.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, recent studies have suggested that women with high levels of AMH are at considerably increased risk of developing OHSS [15,18,38,39]. A clinician may use this information to reduce the starting dose of FSH in such "high risk" patients, thereby reducing their chances of developing OHSS.…”
Section: Discussionmentioning
confidence: 99%
“…Two large randomized trials revealed that AMH is highly predictive of OHSS. A cut-off value of AMH levels ~ ≥3.5 ng/ml had high sensitivities and specificities 11,12 . Lee et al demonstrated that basal AMH and serum E2 on the day of trigger are reliable predictors of OHSS with AMH cut-off value of > 3.36 ng/mL, with sensitivity of 90.5% and specificity of 81.3%.…”
Section: Discussionmentioning
confidence: 99%
“…Other Studies investigated the value of low BMI (low body weight) in the prediction of OHSS with reported contradictory results. Currently BMI is not a useful marker for prediction of OHSS 11,30 . Similarly AFC while significant in the OHSS group, no cut-off value could be obtained (non-significant ROC analysis).…”
Section: Discussionmentioning
confidence: 99%
“…However, using a similar approach, Nardo et al were unable to demonstrate any relationship between serum follicle-stimulating hormone, luteinizing hormone or testosterone and ovarian stromal volume in 23 infertile women with clomiphene citrate-resistant polycystic ovarian syndrome at the same stage of the menstrual cycle [24]. 3D imaging can calculate ovarian volumes more accurately than measurements based on 2D estimations [25], and facilitates detailed follicle counts; this should arguably mean that it becomes the ultrasound technique of choice for diagnosis in the future.…”
Section: Polycystic Ovarian Syndromementioning
confidence: 99%